Characterization of the novel HLA‐C*04:450 allele by next‐generation sequencing. (12th July 2021) - Jacob, Valentine; Usureau, Cédric; Fourdrain, Ludivine; Desoutter, Judith; Guillaume, Nicolas
Abstract : HLA‐C*04:450 differs from HLA‐C*04:01:01 by one nucleotide substitution in codon 328 in exon 7.